Hak Cipta Atas Program Komputer Berdasarkan Hubungan Kerja - Madani, Shailawa Ramb; Yudhantaka, Lintang (Legal Spirit, 2024)
Computer programs, as one of the creations protected through intellectual property rights, are generally created by the initiative of the creator, orders, or based on employment relationships. Creations formed based on employment relationships often lead to disputes over ownership rights. This is related to the party that initiates the idea, the party involved in the creation process, and the supervision and evaluation of the creation. This research uses a normative juridical research method, which examines an issue through literature review with descriptive analytical data analysis methods. The research results indicate that creations designed through an employment relationship require legal certainty regarding the limitations of the employment relationship referred to in the Copyright Law.